Tonsilities – symptoms, causes and diagnosis - Jacek Przybyłowski; Anna Fabian-Danielewska (Journal of Education, Health and Sport, 2019)
Diseases of the throat and tonsils are one of the most frequent causes of patient visits to pediatricians and family doctors. It should be emphasized that to protect the vast majority of them, symptomatic management is sufficient. When applying for pharmacological interventions, the physician should be guided by experience, while supporting himself with objective scientific data confirming the effectiveness of the recommended treatment. It is worth emphasizing the necessity to implement the vaccination calendar as a proven effective method of protecting patients from serious complications of infectious diseases.